Notes on Early Land Plants Today. 61. New synonyms and new combinations in Cephaloziaceae and Cephaloziellaceae (Marchantiophyta) - Vana, Jiri; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
Váňa et al. (2013) published some new combinations and synonyms of Cephaloziaceae and Cephaloziellaceae. In the present note some additional synonyms and combinations based on newly studied material, are presented.